2021
DOI: 10.3390/v13030393
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Characterisation of Human Sapovirus from Children with Diarrhoea in the Rural Areas of Vhembe District, South Africa, 2017–2020

Abstract: Diarrhoeal disease is considered an important cause of morbidity and mortality in developing areas, and a large contributor to the burden of disease in children younger than five years of age. This study investigated the prevalence and genogroups of human sapovirus (SV) in children ≤5 years of age in rural communities of Vhembe district, South Africa. Between 2017 and 2020, a total of 284 stool samples were collected from children suffering with diarrhoea (n = 228) and from children without diarrhoea (n = 56).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The discrepancies in results might be as a result of the setting as reported by [19] whose report in the rural and urban settings presented contradictory results in relation to germ infection as a cause of diarrhea. In corroboration with other studies [4,17,18,20], caregivers (69.3%) cited their understanding and some of the signs associated with diarrhea to be, passing of unformed or watery stool more than three times a day, presence of blood in the stool, abdominal pain as well as nausea/vomiting.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The discrepancies in results might be as a result of the setting as reported by [19] whose report in the rural and urban settings presented contradictory results in relation to germ infection as a cause of diarrhea. In corroboration with other studies [4,17,18,20], caregivers (69.3%) cited their understanding and some of the signs associated with diarrhea to be, passing of unformed or watery stool more than three times a day, presence of blood in the stool, abdominal pain as well as nausea/vomiting.…”
Section: Discussionsupporting
confidence: 84%
“…A major public health concern with regards to caregiver practices with drinking water are the reports of positive cases of sapovirus as well as a high distribution of Enterococcus faecalis and Eschericia. coli as fecal coliform bacteria in all the selected drinking water samples (municipal taps and boreholes, rivers and springs) collected at the point-of-use in study settings located in Vhembe District across all seasons [ 4 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human SV has four well-known genogroups, namely, genogroups I, II, IV, and V. Although SV-GI is the most detected genogroup followed by SV-GII, these genogroups are commonly associated with acute gastroenteritis across age groups and often detected in infants [ 2 , 4 – 8 ]. There are few studies on the detection of human SV in South Africa which have been reported in different settings, that is, on rural outpatients [ 9 ], in a longitudinal study [ 10 ], on urban hospitalized children [ 11 , 12 ], and on all age groups [ 13 ].…”
Section: Introductionmentioning
confidence: 99%